Investigation of Microalgal Carotenoid Content Using Coherent Anti-Stokes Raman Scattering (CARS) Microscopy and Spontaneous Raman Spectroscopy - Legesse, Fisseha Bekele; Rueger, Jan; Meyer, Tobias; Krafft, Christoph; Schmitt, Michael; Popp, Jürgen (ChemPhysChem, 2018)
The yield of high-value products, such as pigments that could be extracted from microalgae, is affected by various nutritional and physical factors. Consequently, there is a need for fast visualization techniques that investigate the responses of individual microalgal cells to changing environmental conditions without introducing perturbations. Here, we apply CARS microscopy to map the distribution of pigments in the diatoms Ditylum brightwellii and Stephanopyxis turris and report their relative change in response to varying light cycles using a marker-based watershed analysis of the acquired images. Simultaneously, the underlying specific pigment composition alterations are revealed using Raman microspectroscopy at 785 nm excitation. In regards to assessing the chemical content of microalgae, these methods present themselves as viable alternatives to the standard techniques currently in use because of their non-disruptive nature and the wealth of complementary information that could be obtained from them.
CRIS-Team Scopus Importer:2023-04-20
Keywords: algae; carotenoids; coherent anti-Stokes Raman scattering; medical and biological imaging; vibrational spectroscopy